Kebijakan Pemerintah dalam Pengelolaan Pertambangan: Menuju Sustainable Development Goals pada Ibu Kota Baru - Ainun Kusuma Dewi, Ainun (Law Research Review Quarterly, 2024)
In an effort to equalize the economy, population, and development, the government moved the capital to East Kalimantan Province. The nation's capital supports the Sustainable Development Goals (SDGs) launched by the United Nations (UN). One of the government's efforts in achieving the goals of the SDGs in building the IKN is the Forest City concept. However, this is not easy considering that East Kalimantan is one of the largest producers of mining resources for Indonesia. This study uses a normative juridical method of statutory approach that is relevant to the issue of mining management in the IKN area. This study finds that mining management in Indonesia, especially in East Kalimantan which will become IKN, must integrate the principles of Sustainable Development Goals (SDGs) to achieve social, economic and environmental welfare in a sustainable manner. The importance of environmentally sound reclamation and post-mining and the enforcement of sanctions for companies that do not comply with regulations are also emphasized. In addition, community oversight is needed to ensure corporate responsibility in mining activities. Government policies that include the granting of mining business licenses (IUP) and guidance are expected to support efficient and accountable management.